Formación técnico-táctica de los luchadores olímpicos españoles - Argudo-Fuentes, C.; López-Gullón, J. M.; Bazaco-Belmonte, M. J.; Vegara-Ferri, J. M.; Angosto, S. (Journal of Sport and Health Research, 2020)
Objectives: The aim of this study was to find out how the technical-tactical work has been carried out in the process of sports training for Spanish Olympic wrestlers. Method. A qualitative methodology was used, carrying out a semi-structured interview with 21 wrestlers. Results. The Olympic wrestlers estimate that they have not worked adequately the technical aspects in the stage of sports initiation, and to a lesser extent the tactics. The own technique in the majority p=15 has developed the classic model. Since the year 2000, according to the criteria of the participants, p=9 are totally in agreement with the new training process, which integrates the technical-tactical components in a logical unit linked to the progressive performance, increasing notably the results in competition. Conclusions. In the training process, the main elements of sports training we find in the first place the technique, simultaneous to tactics as the most important and determining components in high competition to achieve excellence.